Impact of sodium salts on agglomeration in a laboratory fluidized bed. (1st June 2019) - Sevonius, Christoffer; Yrjas, Patrik; Lindberg, Daniel; Hupa, Leena
Abstract: When using biomass as fuel for power and heat production, compounds in the biomass ash may cause problems for fluidized bed boilers, such as corrosion and agglomeration. Especially high alkali biomass has been shown to cause agglomeration that may lead to defluidization. Many laboratory scale studies have been done to clarify which compounds cause agglomeration and to identify actions to minimize the agglomeration tendency. However, most studies have used fuels or ashes; only a few studies using pure alkali salts can be found. To be able to study the agglomeration mechanisms in more detail, pure alkali salts were fed into a quartz bed as a function of time at different bed temperatures. Each test was terminated either at the point of defluidization or after a certain amount of salt had been fed. Samples of agglomerates and bed material were analyzed by SEM/EDX after the tests. The results showed that Na2 CO3 reacted with the bed material to form sodium silicate, while NaCl, as well as Na2 SO4, melted and glued the bed particles together. However, when water was added to the fluidization air, NaCl also reacted with the bed material, forming sodium silicate at temperatures above the melting point of NaCl. The amount of melt causing defluidization was calculated (based on analysis) to be around 0.10–0.13 wt% for the melting compounds. Furthermore, the amount of sodium silicate melt that was formed in the tests with Na2 CO3 was calculated (based on fed Na2 CO3 ) to be much higher (0.59–0.96 wt%) at defluidization.